Dynamic shapes of the zygote and two-cell mouse and human - Chris F. Graham; Shane Windsor; Anna Ajduk; Thanh Trinh; Anna Vincent; Celine Jones; Kevin Coward; Dilraj Kalsi; Magdalena Zernicka-Goetz; Karl Swann; Adrian L. R. Thomas (Biology Open, 2021)
Mouse zygote morphokinetics were measured during interphase, the mitotic period, cytokinesis, and two-cell stage. Sequences of rounder–distorted–rounder shapes were revealed, as were changing patterns of cross section area. A calcium chelator and an actin-disrupting agent inhibited the area changes that occurred between pronuclear envelope breakdown and cytokinesis. During cell division, two vortices developed in each nascent cell and they rotated in opposite directions at each end of the cell, a pattern that sometimes persisted for up to 10 h. Exchange with the environment may have been promoted by these shape and area cycles and persisting circulation in the cytoplasm may have a similar function between a cell's interior and periphery. Some of these movements were sporadically also seen in human zygotes with abnormal numbers of pronuclei and the two-cell stages that developed from these compromised human zygotes.